PRIMORSKIJ TERRITORIAL ADMINISTRATION HEALTH DEPARTMENT WORK ORGANIZING TO PREVENT SPREADING OF SEVERE ACUTE RESPIRATORY SYNDROME - V. G. Ushakov; G. P. Gorshunova; M. F. Kinyaikin; N. A. Belogolovkina; N. A. Pavlikova (Acta Biomedica Scientifica, 2020)
Measures for SARS spreading prevention in treatment-and-prophylactic institutions of Primorski territoryand the experience of the pneumonia monitoring of different etiology are presented. The approaches for early detection of patients with SARS are determined.